Investigation of a spray cooling system with two nozzles for space application. (5th October 2015) - Wang, Ji-Xiang; Li, Yun-Ze; Zhang, Hong-Sheng; Wang, Sheng-Nan; Mao, Yu-Feng; Zhang, Ya-Nan; Liang, Yi-Hao
Abstract: This paper presents a novel spray cooling system applicable to space thermal management systems. Using porous foamed copper, this cooling system is integrated with phase-change microfluidic cooling tactics, able to realize liquid loop control and vapor–liquid separation (VLS) in microgravity due to capillary forces and superhydrophilicity. The present research is composed of two parts. Mathematical models of the liquid loop in the system were established in Part I. Optimal analysis for flow characteristics was conducted in order to apply terrestrial thermal experimental results to space application and to attain a relative optimal fluidic COP (FCOP). Based on part I, part II encompassed the building of experimental setup as a prototype and implementing ground-based experiments to study the spray cooling performance. Effects of mass flow rate and spray distance upon heat transfer characteristics of the system were investigated. Heat transfer mechanism was examined and all the experimental results were discussed as well. We found two relative optimal operating conditions for this given system in terms of the maximum critical heat fluxes (CHF) and effectiveness of spray cooling at CHF respectively. Highlights: Spray cooling system integrated with porous foamed copper. Experiments can be applied to predict the operating behavior in space application. Effect of capillary forces enables the system a high fluidic COP. There are an optimal flow rate and optimal orifice-to-surface distance.